(untitled) (Research, Society and Development, 2023)
Objective: to analyze the interaction of cannabidiol (CBD) with Nav1.7 and compare it with carbamazepine (CBZ) through molecular docking. Methodology: a quantitative and experimental research, of the in silico type, which used CBD (CID: 644019) and CBZ (CID: 2554, standard drug blocker), anticonvulsant used in chronic pain, on the Nav1.7 channel (PDB: 6N4I), as target protein. Docking simulations were obtained using the Dockthor®, analyzed and visualized using UCSF Chimera®. The results of the CBD and CBZ simulations were arranged in order of highest affinity with the channel protein. The affinities scores were compared using the Student t-test in the GraphPad Prism®, where p values p < 0.05 were considered significant. Results: 1,000,000 evaluations of the possible interactions of CBD and CBZ with Nav1.7 were carried out, which the best three with the lowest binding energy (kcal/mol) were selected. The predicted binding affinity scores of Nav1.7 protein and CBD, and CBZ were - 8.61 ± 0.008 and - 8.47 ± 0.27, respectively. Comparing these values, it was noted that affinities did not difference significant (p = 0.31), which is reflected in the similar positions of each one in the channel and possible therapeutic potency. CBD is hydrogen bonded to THR180 residue with the distance of 1.86 Å. Conclusions: cannabidiol binds to Nav1.7, being able to block it. These data support the clinical use of cannabidiol as an analgesic through the neuronal inhibitory pathway.